Trying to Make Cracks in the Mexican Educational System: the counterpoints in the learning of the students of the Degree in Rural Development Planning of the Centro de Estudios para el Desarrollo Rural (CESDER) in the North Mountain of Puebla - Germán Ortiz Palomeque (Universidade Federal do Rio Grande do Sul, 2022)
This document reviews an alternative and genuine higher education model that sustainably supports learning processes through the experiences lived by students of the Rural Development Planning course at the Centro de Estudios para el Desarrollo Rural (CESDER), located in Sierra Norte de Puebla. For this purpose, the ethnographic approach was used based on interviews in situ in which each of the seven students (three women and four men) described how their learning has been, the experiences in their educational institution, and how these processes influenced in their livelihoods. In-depth interviews were also conducted with two CESDER teachers who described the work philosophy assumed in this house of studies. It is found that education under the CESDER approach has influenced their livelihoods because the field experiences critically reflected in the classroom are interrelated with the teaching perspectives, and with the knowledge of the peasants to generate communities of situated learning.